Injury epidemiology of tennis players at the 2011-2016 Australian Open Grand Slam - Gescheit, D. T.; Cormack, S. J.; Duffield, R.; Kovalchik, S.; Wood, T. O.; Omizzolo, M.; Reid, M. (British Journal of Sports Medicine, 2017)
Aim: To examine the epidemiology and in-event treatment frequency of injury at the 2011-2016 Australian Open tournaments.